Fighting Public School Crisis: My Role as a School Leader [Principal] During COVID-19 Pandemic: The Challenges and Strategies of School Leadership in the COVID-19 Pandemic (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A crisis is an unstable time in which a decisive change is awaiting, especially with the divergent possibility of extremely undesirable outcomes. Given the exacerbated inequality in primary and secondary education student access and learning which had already been observed and reported extensively by news media, the COVID-19 pandemic unquestionably qualifies as a public education crisis. School leadership in times of disaster requires strategically and delicately balancing sensitive relational skills with effective and efficient leadership competencies. The COVID-19 pandemic, bringing to the forefront and catalyzing long-unconfronted educational inequities, in addition to economic fall down and deep political differences - which all impact students and schools – has resulted in a complex crisis that requires a fresh conceptualization of school leadership during times of crisis.